Twin pregnancy in the unicornuate uterus and non-communicating rudimentary horn: A case report - Hafizi, Leili (Int J Reprod Biomed, 2019)
Background: A unicornuate uterus is present in 0.1% of the general population. This müllerian anomaly carries significant obstetrical risk including abortion, preterm delivery, and rudimentary horn ruptures. Case: The patient is a 24-yr-old primigravida with 12-wk gestational age and a twin pregnancy in the unicornuate uterus and non-communicating rudimentary horn. One fetus in the unicornuate uterus and other in the rudimentary horn that was ruptured. In urgent laparotomy rudimentary horn and fallopian tube excised. Pregnancy in the unicornuate uterus was continued and at 38-wk gestational age, cesarean section due to premature rupture of the membrane was performed and then normal fetus was delivered. Conclusion: Twin pregnancy in a unicornuate uterus and rudimentary horn is a rare condition that carries a considerable risk to the mother. There is a need for increased awareness of this rare condition to prevent maternal morbidity and mortality.